Pemanfaatan Aplikasi E-Learning Dalam Meningkatkan Proses Belajar Mengajar Guru Dan Siswa - Nana Suarna; Nining Rahaning; Ade Awaludin; Adinda Aulia Putri (CV. Multi Kreasi Media, 2023)
The Covid-19 pandemic has accelerated the adoption of technology in education, particularly the use of e-learning applications. However, a lack of digital skills and understanding among teachers and students remains a major challenge. This Community Service Program aimed to improve digital literacy through training in the use of e-learning platforms. Activities were carried out in several stages: needs assessment, socialization, training, mentoring, and evaluation. The training materials included the introduction to platforms such as Google Classroom and Moodle, digital class management, content development, and online assessment. The results showed a significant improvement in the skills of both teachers and students in utilizing e-learning tools. Teachers became more confident and capable of integrating technology into their teaching processes, while students became more independent and active in online learning. Additionally, the training modules and video tutorials developed during the program served as sustainable learning aids. Online discussion forums were also established to facilitate experience sharing and technical problem-solving collaboratively. This program not only had a positive impact on participants’ technical competencies but also changed their mindset regarding technology use in education. Sustainability is recommended through continued training, infrastructure improvement, and collaboration with various stakeholders. Thus, this initiative is expected to become a model for sustainable digital literacy development in educational settings, particularly in regions that are lagging behind in adopting educational technology.